ANALYSIS OF CSR DISCLOSURE, EARNINGS PERSISTENCY, EARNINGS GROWTH, AND BUSINESS SIZE ON EARNINGS MANAGEMENT WITH INSTITUTIONAL OWNERSHIP AS A MODERATING VARIABLE (Case Study on LQ45 Companies Listed on the Indonesia Stock Exchange (IDX) 2016-2020) - Setiawati, Erma; Sekarningrum, Alifah; Witono, Banu (Riset Akuntansi dan Keuangan Indonesia, 2022)
Due to a lack of development, Indonesia’s border areas are often undeveloped. This research aims to determine the impact of CSR disclosure, earnings persistence, earnings growth, and business size as factors influencing earnings management in LQ45 companies listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020. Multiple linear regression with SPSS 25 was employed to analyze the data. The findings disclosed that CSR disclosure, earnings persistence, and business size all impacted earnings management. However, earnings growth did not affect earnings management. Testing with the moderating variable revealed that CSR disclosure and business size, moderated by institutional ownership, influenced earnings management. Moreover, earnings persistence and earnings growth variables, moderated by institutional ownership, did not affect earnings management.